1993
DOI: 10.1248/cpb.41.1434
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oleic Acid/Propylene Glycol on Rat Abdominal Stratum Corneum: Lipid Extraction and Appearance of Propylene Glycol in the Dermis Measured by Fourier Transform Infrared/Attenuated Total Reflectance(FT-IR/ATR) Spectroscopy.

Abstract: Fourie transform infrared/attenuated total reflection analysis demonstrated that the absorbance intensity of C = O stretching bands, which reflect the amounts of lipids in the stratum corneum, decreased with an increase in the duration of skin treatment with 0.15 M oleic acid/propylene glycol (PG) system, suggesting that the oleic acid/PG system induced the lipid extraction, which was followed by a reorganization of the stratum corneum structures. The spectral peaks which originated from the PG molecule were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 0 publications
1
17
0
Order By: Relevance
“…15 C18:1/EtOH has also shown to cause extensive lipid extraction. 51 Takeuchi et al 52 found, using IR spectroscopy, that C18:1/PG treatment of rat skin produced time dependent extraction of SC lipids. This especially would create a void volume to allow permeation of solutes during iontophoresis.…”
Section: Resultsmentioning
confidence: 99%
“…15 C18:1/EtOH has also shown to cause extensive lipid extraction. 51 Takeuchi et al 52 found, using IR spectroscopy, that C18:1/PG treatment of rat skin produced time dependent extraction of SC lipids. This especially would create a void volume to allow permeation of solutes during iontophoresis.…”
Section: Resultsmentioning
confidence: 99%
“…The combined infrared spectroscopy and DSC results suggest that certain exogenously applied fatty acids can disrupt the stratum corneum lipid structure and increase motional freedom or fluidity of the lipids. 8,16) It is not clear from these results, however, whether structural differences seen among the various acids are due to their relative disrupting power or simply reflect varied uptake of these compounds by the stratum corneum. Therefore further studies need to be conducted to clarify this.…”
Section: )mentioning
confidence: 93%
“…1,2) The ability of OA to enhance percutaneous absorption has long been known. 3,7,8) It appears that the stratum corneum lipids constitute the epidermal permeability barrier, and that disruption of this stratum corneum lipid structure will put the skin barrier at risk. Recent results obtained with attenuated total reflectance infrared spectroscopy suggest that the action of OA could be due to both mechanisms, i.e., lipid fluidity and lipid phase separation.…”
Section: Ultrastructural Observationsmentioning
confidence: 99%
“…It was observed that pH could affect the abundance of Subgroups 3, 4, 6 and 7 [38,43]. Moreover, some orders showed slight decrease in the compositional proportion in the eCO 2 treatment (Figure 2), for instance Sphingomonadales, a kind of obligate aerobe that can produce catalase [44] and convert hydrogen peroxide into water and oxygen to eliminate the negative effects of peroxide to other microbes. Therefore, we suggest that oxygen content may be altered under the eCO 2 conditions and this could lead to a decline in the relative abundance of aerobic microbes such as Sphingomonadales in the soil.…”
Section: Effects Of Elevated Co 2 On Soil Carbon and Associated Microbesmentioning
confidence: 99%